Use of human pluripotent stem cell-derived cells for neurodegenerative disease modeling and drug screening platform - García-León, Juan Antonio; Vitorica Ferrández, Javier; Gutiérrez-Pérez, Antonia (Taylor and Francis, 2019)
Most neurodegenerative diseases are characterized by a complex and mostly still unresolved pathology. This fact, together with the lack of reliable disease models, has precluded the development of effective therapies counteracting the disease progression. The advent of human pluripotent stem cells has revolutionized the field allowing the generation of disease-relevant neural cell types that can be used for disease modeling, drug screening and, possibly, cell transplantation purposes. In this Review, we discuss the applications of human pluripotent stem cells, the development of efficient protocols for the derivation of the different neural cells and their applicability for robust in vitro disease modeling and drug screening platforms for most common neurodegenerative conditions
Keywords: Alzheimer, Enfermedad de; iPSC